Two sides of Ukrainian philosophy (Actual Problems of Mind, 2017)
The author explicates a co-existence of the two sides of Ukrainian philosophy: a purely domestic existential-antropological one and an European rationalistic one.
Keywords: National philosophy; syncretism; existentialism; cordocentrism